Lower extremity hemorrhage in patients with spinal cord injury receiving enoxaparin therapy. (March 2015) - Yeung, Vincent; Formal, Christopher
Abstract : Low-molecular-weight heparin is commonly favored over unfractionated heparin because of its predictable pharmacokinetic and pharmacodynamic properties. However, full-dose enoxaparin can cause major soft tissue bleeding that may lead to compartment syndrome and even limb amputation. In patients with spinal cord injury, range of motion exercises should be carefully performed if on full-dose enoxaparin. This vulnerable patient population is particularly susceptible to aggressive stretching, which could lead to bleeding, and compartment syndrome. Providers should also monitor weight fluctuations in patients receiving full-dose enoxaparin. Changes in weight without proper dose adjustment can cause over or under treatment. Attention to both these issues can improve patient care.